La educación musical y su incidencia en el desarrollo socio-afectivo de los niños y niñas de 5 a 6 años de la escuela de educación básica José Miguel Burneo Burneo de la ciudad de Loja, periodo 2014 - Lima Ontaneda, Diana Paola (2015)
This thesis refers to: THE MUSICAL EDUCATION AND ITS IMPACT ON SOCIO- EMOTIONAL DEVELOPMENT OF CHILDREN 5 TO 6 YEARS FOR BASIC EDUCATION SCHOOL OF JOSÉ MIGUEL BURNEO BURNEO CITY LOJA, PERIOD 2014. Was raised as a general goal: Raise awareness among teachers about the importance of music education in the Socio - Affective of children of 5-6 years of the School of Basic Education José Miguel Burneo Burneo City of Loja, period 2014. The methods used were : scientific , inductive -deductive , analytic-synthetic , descriptive, and statistical techniques : A psychology applied to interview teachers and León Gross Ebee test for the socio- emotional development of children , applied to parents. The population consisted of a total of 26 children, 26 parents and 2 teachers from the School of Basic Education José Miguel Burneo Burneo. From the information obtained through the application of techniques and instruments came to the conclusion that ; 2 Master representing 100% said that music education if affects the socio- emotional development of children; 2 Master representing 100% said nursery rhymes if you help improve the teaching-learning process thus enhancing their overall development. Also we have 6 children representing 23% had a high level in their socio- affective, 18 children representing development achieved a 69% average and 2 children representing 8% had a low level. This lets us know that most children have a medium development, the children are developing in a suitable environment according to their age, and there is a real interest from parents to their children.